Effect of phosphate solubilizing and nitrogen-fixing bacteria on Pontianak siam citrus (Citrus ×nobilis var. microcarpa) seed germination - RETNO FIKRIA IDIL ADHYANINGTYAS; RAHMAWATI RAHMAWATI; MUKARLINA MUKARLINA (Smujo International, 2023)
Abstract. Adhyaningtyas RFI, Rahmawati, Mukarlina. 2023. Effect of phosphate solubilizing and nitrogen-fixing bacteria on Pontianak siam citrus (Citrus ×nobilis var. microcarpa) seed germination. Nusantara Bioscience 15: 245-250. West Kalimantan is one of Indonesia's largest producing areas for Siam citrus (Citrus ×nobilis var. microcarpa Hassk.). It is necessary to carry out the proper treatments within the early stages of planting, which increases the speed of germination of citrus seeds to quickly increase the number of seedlings. The biological agents that play a role in promoting plant growth are a group of Plant Growth-Promoting Rhizobacteria (PGPR), consisting of Phosphate-Solubilizing Bacteria (PSB) and Nitrogen-Fixing Bacteria (NFB). This study aims to determine the effect of a combination treatment or a single treatment of phosphate-solubilizing and nitrogen-fixing bacteria, which is known to obtain the best results in the germination and growth of Siam citrus seeds. The study was conducted in a nonfactorial, Completely Randomized Design (CRD). The given treatments were control (without bacterial inoculum), nitrogen-fixing bacteria (NFB P1), phosphate solubilizing bacteria (PSB P2), a combination of NFB and PSB bacteria with a ratio of 1:1 (P3), a combination of NFB and PSB bacteria with a ratio of 2:1 (P4), and the combination of NFB and PSB bacteria with a ratio of 1:2 (P5). Observations were made for 4 weeks after planting. A single treatment with phosphate-solubilizing bacteria (P2) gave the best result on almost all parameters, such as germination percentage, emergence time of germination, root length, number of leaves and fresh weight of Siam citrus seedlings.